2010
DOI: 10.1007/s00701-010-0772-9
|View full text |Cite
|
Sign up to set email alerts
|

Partially thrombosed intracranial aneurysms: symptoms, evolution, and therapeutic management

Abstract: The natural history of PTIAs is different from other aneurysms. They most commonly present with progressive neurological symptoms due to mass effect. MRI properly diagnoses PTIAs and allows precise follow-up, more accurately than angiography because it detects prominent "abluminal" features indicating inflammation and neovascularization. Spontaneous thrombosis is part of the natural history of PTIAs and it should be taken in consideration when discussing the therapeutic management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 28 publications
1
32
0
Order By: Relevance
“…7 Partially thrombosed intracranial aneurysms mostly (60%-91%) present with symptoms of mass effect. 2,8,9 In comparison, embolic phenomena are infrequent. 9 Several patients had nonspecific symptoms, with headache being most common.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…7 Partially thrombosed intracranial aneurysms mostly (60%-91%) present with symptoms of mass effect. 2,8,9 In comparison, embolic phenomena are infrequent. 9 Several patients had nonspecific symptoms, with headache being most common.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Meanwhile, a few other small case series found these aneurysms to be much less vulnerable to recanalization (approximately 30%) following coil embolization. 2,8 They also reported relief of symptoms and stabilization of the clinical evolution of the disease after coiling. Surgery was ruled out in our patients with aneurysms in the posterior circulation, due to their location, size, and circumferential thrombus.…”
Section: 289mentioning
confidence: 91%
See 2 more Smart Citations
“…6,7 Previous MR imaging studies have revealed important morphologic features in these aneurysms, which are only partially assessable by DSA. 8,9 Better delineation and characterization of GAs may help to improve our comprehension of the distinct pathophysiology of this rare aneurysm subgroup. The purpose of this study was to assess GAs and their wall microstructure by 7T MR imaging, previously only visualized in histopathologic examinations.…”
Section: 3mentioning
confidence: 99%